RELATIONSHIP BETWEEN EDUCATIONAL ASPECTS AND ECONOMIC VULNERABILITY OF SMALL AND MEDIUM-SIZED ENTERPRISES (SMEs) FOR ENVIRONMENTAL SOCIAL DISASTERS IN BANDA ACEH - Parmakope, Parmakope; Agussabti, Agussabti; Nizamuddin, Nizamuddin (CV. Radja Publika, 2022)
Social environmental disasters such as natural disasters are events that have a negative impact on people's lives. The coronavirus pandemic disease (Covid-19) is one of them. The effect of Covid-19 has given society to lose its material and non-material properties. Banda Aceh City is one of the affected areas due to the distribution of COVID-19. The economic sector is one of the sectors most affected by the Covid-19 pandemic. Micro, Small and Medium Enterprises (SMEs) have survived and saved the Indonesian economy even during the monetary crisis in 1998. Even so, MSMEs have experienced difficulties facing the Covid-19 pandemic. Based on data from 1,785 cooperatives and 163,713 MSMEs affected by the Corona virus pandemic (COVID-19). Most of the MSMEs affected by COVID-19 are involved in primary needs, such as food and drink. The Banda Aceh City Government issued a social distancing policy to reduce the distribution and spread of COVID-19. However, this research tries to look at what factors, levels, and strategies affect the economic vulnerability of MSMEs during the Covid -19 pandemic period. In the end, economic vulnerability in socio-environmental disasters has been analyzed in relation to educational aspects.